The characteristics of structural concrete using bacteria improvement - Andalib, Ramin (2015)
Concrete is a porous material and its porosity is accompanied by ingress of aggressive agents to decrease its strength and durability. Natural ingredient with filling capacity can be added to concrete to improve its characteristics. There are some natural waste materials which are known as good materials for partial replacement of ordinary Portland cement in the production of concrete. Construction problems and mix design complexity using these waste materials are the reasonable evidences for a need for another type of concrete. In recent times, the application of microorganism in cementations materials has received a lot of interest. One significant area of interest is bacterial concrete. The concept is to introduce bacteria in concrete, which will aid in mineral precipitation of pores and tiny cavity areas. Bacillus is a type of bacteria that can produce as a binding filler material to enhance concrete characteristics. This study provided an insight of a new biotechnological method based on calcite precipitation to improve the strength of structural concrete. It is clear that mineral precipitation has the potential to enhance construction material resistance towards degradation processes. Different cell concentrations of bacteria from 103 to 107cfu/ml were introduced in concrete and significant increase in the compressive strength was obtained in the case of 105cfu/ml at different ages. Subsequently, to the structural concrete, five different cell concentrations of bacteria (10×105 to 50×105cfu/ml) were introduced and significant increase in the compressive and flexural strength were obtained when 30×105cfu/ml of bacteria was added to concrete at different ages (7, 14, 28 and 60 days). This appropriate cell concentration (30×105cfu/ml) was applied again to the various grades of structural concrete (30, 35, 40, 45, and 50MPa) by mixing water (per ml) in the current experimental approach. It was found that the compressive strength of the higher grade of structural bacterial concrete has improved as compared to lower grade due to more precipitation of calcite. In order to study the durability of structural concrete against aggressive agents, specimens with appropriate cell concentration were immersed in different types of acids solution (sulphuric and hydrochloric acids) to compare their effects on 60th, 90th and 120th day. The experiment demonstrated that bacterial concrete had decreased in weight and strength losses when compared to the ordinary Portland cement concrete without bacteria as control, especially in the highest grade of structural bacterial concrete (50MPa).It was also found that maximum compressive strength and weight loss occurred during sulphuric acid immersion. Microbial calcite precipitation was also quantified by X-ray diffraction (XRD) analysis, visualized by scanning electron microscopy (SEM) and analysed by energy dispersive spectrometer (EDS). An increase in density and uniformity of bacterial concrete was observed compared to the ordinary Portland cement concrete because of calcite deposition. Eventually, it was discovered that addition of Bacillus species bacteria had a positive effect on the strength and durability of structural concrete